An Impact of the Introduction of ThaiDEX SET50 ETF on SET50 Index Spot-Futures Arbitrage Efficiency - Chiarawongse, Anant (Creative Business and Sustainability Journal, 2017)
Abstract In 2007, Stock Exchange of Thailand lists ThaiDEX SET50 Exchange Traded Fund (TDEX), its first equity Exchange Traded Fund (ETF) that is designed to track SET50 index. Futures contracts with SET50 index as the underlying asset are in existent since 2006. This paper studies an impact such a listing of TDEX might have on index arbitrage activity. In a market without friction, mispricing between futures and the underlying index should be eliminated instantaneously by arbitrageurs. As a result, futures prices and index level will have a certain relationship according to the cost-of-carry model. However, in a real market situation, what seems like mispricing might persist due to limits to arbitrage. Since the introduction of TDEX can potentially relaxes some of those limits, we expect the mispricing to be less persistent after the introduction of TDEX. To quantitatively measure the responsiveness that prices adjust to mispricing, we apply an error correction model to daily data of SET50 index futures and SET50 index. The coefficient of the error term in the model, which is called speed of adjustment coefficient, is a natural measure of speed that prices adjust to reach equilibrium. If the availability of TDEX helps facilitating arbitrage transactions, then the speed of adjustment coefficient is expected to increase after the listing of TDEX. Keywords: Arbitrage, ETF, Cointegration, Error Correction Model บทคัดย่อ ในปีพ.ศ. 2550 ตลาดหลักทรัพย์แห่งประเทศไทยได้เปิดให้ซื้อขาย ThaiDEX SET50 ซึ่งเป็นกองทุนรวมที่จดทะเบียนซื้อขายในตลาดหลักทรัพย์ (อีทีเอฟ) ที่ออกแบบให้มีผลตอบแทนตามดัชนี SET50 สัญญาฟิวเจอร์ที่อ้างอิงดัชนี SET50 เช่นเดียวกัน ได้เปิดให้ซื้อขายตั้งแต่ปีพ.ศ. 2549 บทความนี้ศึกษาว่าการเปิดให้ซื้อขาย TDEX มีผลกระทบต่อการทำอาบิทราจบนดัชนีหุ้นอย่างไร ในตลาดที่ไม่มีความฝืด ส่วนต่างราคาที่ผิดปรกติระหว่างฟิวเจอร์และดัชนีอ้างอิงควรจะถูกทำกำไรทันทีโดยผู้ทำอาบิทราจ ดังนั้นราคาฟิวเจอร์และระดับดัชนีควรจะมีความสัมพันธ์ที่เป็นไปตามตัวแบบต้นทุนการถือครอง แต่ในสภาพตลาดจริง ส่วนต่างราคาที่ผิดปรกติอาจจะคงอยู่ได้เป็นเวลานาน อันเป็นผลข้อจำกัดในการทำอาบิทราจ เนื่องจากการเปิดให้ซื้อขาย TDEX อาจช่วยลดข้อจำกัดในการทำอาบิทราจให้น้อยลง ผู้เขียนคาดหมายว่าส่วนต่างราคาที่ผิดปรกติจะคงอยู่ได้สั้นลงหลังจากการเปิดให้ซื้อขาย TDEX ผู้เขียนใช้ตัวแบบตอบสนองความคลาดเคลื่อนกับข้อมูลราคารายวันของสัญญาฟิวเจอร์บนดัชนี SET50 และค่าของดัชนี SET50 ในการวัดการตอบสนองของราคาต่อส่วนต่างราคาที่ผิดปรกติ ค่าสัมประสิทธิ์ของพจน์ค่าความคลาดเคลื่อนซึ่งมีชื่อเรียกว่า สัมประสิทธิ์ความเร็วในการปรับตัว เป็นตัววัดความเร็วที่ราคาปรับตัวเข้าสู่ค่าที่ควรจะเป็น ดังนั้น ถ้าการมี TDEX ช่วยให้ทำอาบิทราจได้ง่ายขึ้น ผู้เขียนคาดหมายว่า สัมประสิทธิ์ความเร็วในการปรับตัวควรจะมีค่าเพิ่มขึ้นหลังจากการเปิดให้ซื้อขาย TDEX คำสำคัญ: อาบิทราจ อีทีเอฟ โคอินทิเกรชั่น ตัวแบบตอบสนองความคลาดเคลื่อน